Recommendations for Physical Medicine and Rehabilitation to Impro ve Systemic Lupus Erythematosus Related Sarcopenia: A Literature Review - Defi, Irma R.; Profita, Jeane Claudia; Arisanti, Farida; Charismawati, Septiana (Current Rheumatology Reviews, 2023)
Background: Systemic lupus erythematosus (SLE) is currently the most prevalent autoimmune disorder worldwide. A previous study reported the frequency of sarcopenia in patients with chronic inflammation and found a higher rate of sarcopenia in patients with SLE than in control. A preview study found that exercises management given to SLE patients can reduce fatigue and increase vitality. Objective: The objective of this study is to understand the relationship between sarcopenia and SLE from Physical Medicine and Rehabilitation (PM&R) standpoint and its intervention. Methods: Using the PubMed computer-aided search engine specific keywords: “sarcopenia” AND “Systemic lupus erythematosus” OR “lupus” OR “SLE” OR “physical medicine and rehabilitation” OR “rehabilitation” OR “physical therapy” OR “exercises” OR “physical activity” OR “training” OR “nutrition” OR “OR “diet.” Results: Exercise rehabilitation can increase energy level, cardiovascular fitness, functional status, and physical capabilities of muscle strength and are safe to be performed by patients with SLE. Resistance training has been shown to improve muscle strength and size, increase mitochondrial content, and reduce oxidative stress. Resistance exercise impacts sarcopenia through several mechanisms in the muscular and neuromotor levels. Aerobic exercises are also beneficial for skeletal muscles to increase mitochondrial bioenergy, improve insulin sensitivity, and reduce oxidative stresses. Nutritional interventions such as protein, amino acids, essential fatty acids, and vitamin D produce biological effects that will enhance the physiological adaptation of exercise. Conclusion: Intervention for maintaining muscle function in the prevention and management of sarcopenia in SLE and its complications is a combination of resistance training and nutritional intake through adequate protein intake.
Keywords: sarcopenia